A Psychological Study of the Characters in the Novels of Hijab Imtiaz Ali - Kallu, Parveen; Iqbal, Mazhar; Umar, Muhammad (sourcecoder, 2024)
In Urdu fiction, Hijab Imtiaz Ali had the same importance as Ismat Choghatai in the immediate later period and both these women were styled and unique fiction writers. Hijab was brilliant. Their study is wide, observation and experience are also very sharp and deep, so they reflect public life, but they have no special connection with public life. Although he led a rich social life, his characters do not show this quality of life. His characters deal with life's problems thoughtfully and sometimes gets swept away in a flood of emotions. They are the epitome of nobility and seriousness. Although his characters are familiar to every fiction and novel, they are imaginative, high and civilized society and have unusual qualities. In her novels "Zalim Muhabbat", "Andhera Khwab" and "Pagal Khana"are included. Hijab Imtiaz Ali's last novel, "Pagal Khana", was awarded the Adamji Adabi Award and the Government of Pakistan awarded him the Star of Distinction in recognition of his valuable literary services.